SOLUTION OF PROBLEMS IN OPTIMIZING TRANSPORT LOGISTICS USING GRAPH SCHEMES - Abduvalova А.Д.; Abdimomynova М.М. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The article discusses models and methods for optimizing transport and logistics systems and their elements in the context of market development, which determine a decisive role in the development of logistics. Modern theory and numerical optimization methods are a tool that allows you to make scientifically grounded decisions when driving vehicles using methods and models, quickly and with little resources and time to adapt to changes in the volume of the relevant sectors of transport services. The article discusses a method for optimizing the mode of logistics systems using computer technologies, in order to increase the level and organization of management of transport and logistics systems with state correction. Directed graph allows you to automate the choice of the smallest way of delivery of goods in a transport network with a complex route, carried out on the basis of the calculated graph,taking into account the specified quality criterion. The paper presents an optimization algorithm for the implementation of the method and a computer calculation to reduce the time for performing transport work.